(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
African HE is facing immense obstacles at beginning of latest millennium. Not only is demand for access unstoppable, particularly in context of Africa’s usually low post-secondary attendance levels, but higher education is recognized as a key force for modernization development. The beginning of 21st century is regarded as an era of learning, and higher education has to play a central role. In this article, we focus on some of the main challenges of African higher education. It’s hard to generalize about such a vast and diverse continent as Africa. There are, however, some common elements–and there are certainly some common problems. The hope for future is well guarded, given the complex problems currently facing higher education on the continent. The truth is that under very difficult circumstances, African universities are currently operating, and it will not be an easy road to future success. To order to thrive economically, culturally and politically, Africa must have strong post-secondary sector academic institutions are crucial to the future. Higher education is again regarded as a critical field of African growth after nearly two decades of being shunned by national governments and international agencies.